Prevalence Analysis of Acute Hepatopancreatic Necrosis Disease (AHPND) in Vannamei Shrimp (Litopenaeus vannamei) by PCR Method in Bengkalis District - Ayunda, Fadhilah Putri; Feliatra, Feli; Thamrin, Thamrin; Muhson, Nanang (Journal of Coastal and Ocean Sciences, 2023)
Vannamei shrimp is one of the shrimps that are being cultivated in Indonesia because it has superior quality compared to other types of shrimp. Cultivation activities cannot be separated from disease attacks that attack cultured commodities. One of the diseases that attack vannamei shrimp is Acute Hepatopancreatic Necrosis Disease (AHPND). The disease is caused by Vibrio parahaemolyticus bacterial infection (VpAHPND) which produces toxins and causes death in shrimp with mortality reaching 100%. Therefore, it is necessary to conduct research or early detection in the aquaculture area of Bengkalis Regency using the PCR (Polymerase Chain Reaction) method. The method used is the survey method. This research was conducted from March to April 2023. The results of this study are the prevalence of AHPND (Acute Hepatopancreatic Necrosis Disease) in vannamei shrimp (Litopenaeus vannamei) in the Bengkalis Regency Aquaculture area is 0% with the category of infection never. AHPND examination by PCR method using AP4 primer measuring 230 bp showed that vannamei shrimp samples from Bengkalis District, Bantan District, and Bukit Batu District of Bengkalis Regency were negative for AHPND. The morphological condition of vannamei shrimp from the three research locations did not show any clinical symptoms of shrimp infected with AHPND.